印尼本地汉语教师课堂话语分析 —以 Tri Ratna 和 Budi Agung学校两位初中教师为例 - Shihping Chan; Symphony Akelba Christian; Larry Larry (Asosiasi Program Studi Mandarin Indonesia, 2022)
摘要课堂上，教师话语是教师组织课堂的一项基本专业技能，教师科学有效的使用课堂话语关系着学生课堂学习的效果。在对外汉语教学中，教师的课堂话语是学习者目的语输入的主要的途径。尤其是在印尼国内教授汉语时，学生处在自己的母语环境中，课堂几乎成为他们接触汉语的唯一场所，因此教师得在课时量不多的情况下，需要不断优化和调整自身课堂话语的使用能力，尽可能多为学生提供开口说汉语的机会，因而透过本研究来了解目前教师的课堂用语情况如何和存在什么样的问题。因此，对印尼 Tri Ratna School 和 Sekolah Budi Agung 两所初中一年级的汉语课堂进行录影，并整理课堂教师话语逐字稿语料，以量化语料标记与统计来厘清方向，再质化参与观察，最后透过对教师访谈来了解课堂的脉络，同时对比课堂话语相关理论，来分析课堂话语量、话语构成类型、课堂提问以及课堂反馈的情况，以作为未来印尼本地汉语教师的反思和本地汉语教师培训的相关参考依据。 关键词: 印尼；汉语教师；课堂话语 AbstractIn the classroom, teacher discourse is a basic professional skill for teachers to organize classes and use lessons scientifically and effectively. Classroom discourse is related to the effectiveness of students' classroom learning. For a foreign language learner, the teacher's classroom discourse is the learner's main way to enter the language. Especially when teaching Chinese in Indonesia, Chinese classes have almost become the only Chinese environment to students. Chinese Teachers have to standardize and adjust their classroom discourse and provide students with as many opportunities to speak Chinese as much as possible. This study started with the videos of the first-grade Chinese language classes at Tri Ratna and Budi Agung high school in Indonesia and organize the corpus of the classroom teacher's discourse verbatim manuscript. Then to quantify corpus markers and statistics to clarify the direction, and re-qualitative participation in observation. Through interviews with teachers, we can understand the context of the classroom. At the same time, we compare the relevant theories of classroom discourse to analyze the quantity of classroom discourse, the types of discourse composition, classroom asking, and classroom feedback. The result will serve as a future local Chinese teacher in Indonesia reflections and references for local Chinese teacher training courses.Keywords: Indonesia ; Chinese Teacher ;classroom discourse